Development and psychometric evaluation of an emotional growth questionnaire for university students - Fatemeh Rostami; Jamileh Mokhtari Nouri; Abbas Ebadi; Morteza Khaghanizade (Health Promotion Perspectives, 2018)
Background: Despite the importance of emotional growth promotion among students, there is still a lack of standard emotional growth tools to evaluate the concept while developing interventional programs. The aim of present study was to devise and provide a valid and reliable instrument for measuring students’ emotional growth.Methods: This study was conducted from 2016 to 2017 among university students. A questionnaire containing 79 items was made using focus group discussions with students and studying relevant texts. Exploratory factor analysis (EFA) (n = 188) was used to determine the construct validity of the questionnaire. Confirmatory factor analysis (CFA) (n = 38) was performed to assess the validity of the model. Reliability (n = 56) and repeatability (n = 31) of the questionnaire were assessed.Results: A 4-factor (positive identity, self-esteem, effective communication and motivation)and 21-item solution was found as the best solution, which explained 63.5% of total variancebetween the items. The results of CFA approved the validity of the model (CFI = 0.914, RMSEA= 0.070). Cronbach alpha (0.93) and Intra class correlation coefficient (0.91) approved the reliability and repeatability of questionnaire.Conclusion: The 21 items questionnaire seems to be a valid and reliable instrument to measure emotional growth among university students.